2010
DOI: 10.1371/journal.pone.0013353
|View full text |Cite
|
Sign up to set email alerts
|

AGT M235T Genotype/Anxiety Interaction and Gender in the HyperGEN Study

Abstract: BackgroundBoth anxiety and elevated heart rate (HR) have been implicated in the development of hypertension. The HyperGen cohort, consisting of siblings with severe and mild hypertension, an age-matched random sample of persons from the same base populations, and unmedicated adult offspring of the hypertensive siblings (N = 1,002 men and 987 women), was analyzed for an association of the angiotenisinogen AGTM235T genotype (TT, MT, MM) with an endophenotype, heart rate (HR) in high and low anxious groups.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Six consecutive BP measurements were made during the study visit, three on the left and three on the right arm. The participants rested for 5 min before measurement and for 30 s between measurements (Knox et al, 2010 ). An average sitting systolic blood pressure (SBP) and diastolic blood pressure (DBP) was calculated based on the second and third measurements in the second arm.…”
Section: Methodsmentioning
confidence: 99%
“…Six consecutive BP measurements were made during the study visit, three on the left and three on the right arm. The participants rested for 5 min before measurement and for 30 s between measurements (Knox et al, 2010 ). An average sitting systolic blood pressure (SBP) and diastolic blood pressure (DBP) was calculated based on the second and third measurements in the second arm.…”
Section: Methodsmentioning
confidence: 99%
“…Also, VO2max training response (%) was computed for the g-PAT. Since it has been shown that the major determinants of the VO2max training responses are their own baseline values (genetic influences) 14 and that trait anxiety is a risk factor related to cardiovascular diseases, 23,35 an analysis of covariance (ANCOVA) was performed to confirm the effectiveness of PAT and the contribution of covariates on the improvement participants' VO2max. The independent variable was the experimental training program (g-PAT and g-CON) and the dependent variable consisted of values on VO2max training response.…”
Section: Weeks Of Training Exercise Durationmentioning
confidence: 99%
“…επιβεβαιώθηκαν και σε μελέτη με Αιγυπτιακό πληθυσμό. Η παρουσία του αλληλίου Τ, του Μ235Τ, σε ετεροζυγωτία ή ομοζυγωτία αύξανε τον κίνδυνο εμφάνισης ιδιοπαθούς υπέρτασης133 .Μια μελέτη έδειξε ότι οι πολύ αγχώδεις άνδρες που είχαν το γονότυπο ΤΤ, είχαν αυξημένο κίνδυνο εμφάνισης υψηλής αρτηριακής πίεσης, ενώ ο γονότυπος ΜΜ φαινόταν να είναι προστατευτικός134 .Με τον πολυμορφισμό Μ235Τ σχετίστηκαν οι μεταβολές στη διαστολική αρτηριακή πίεση, κατά τη διάρκεια εξάσκησης κάτω από το μέγιστο δυνατό επίπεδο έντασης σε υγιείς. Οι συμμετέχοντες που έφεραν το γονότυπο ΤΤ δεν είχαν αύξηση της διαστολικής αρτηριακής πίεσης σε σχέση με τους άλλους δύο γονοτύπους ΜΜ και ΜΤ, για τους οποίους καταγράφηκαν αυξήσεις135 .…”
unclassified